The Effectiveness of the STAD Type Cooperative Learning Model on Student Learning Outcomes: Systematic Literature Review (SLR) with the PRISMA Protocol - Dhea Ayu Anggraini; Aynin Mashfufah; Sri Rahayuningsih; Dedi Kuswandi; M. Ramli (Eduvest - Journal of Universal Studies, 2025)
This systematic literature review (SLR) examines the effectiveness of the Student Teams Achievement Divisions (STAD) cooperative learning model in enhancing student learning outcomes, motivation, and social skills across various educational levels and subjects. Guided by the PRISMA protocol, the study analyzed 35 peer-reviewed articles published between 2019 and 2024. Findings reveal that STAD significantly improves academic performance, collaboration, and engagement, particularly for lower-achieving students, by fostering interactive, student-centered learning environments. The integration of supplementary media (e.g., videos, games) further amplifies these benefits. Compared to conventional methods, STAD demonstrates superior outcomes in promoting critical thinking and active participation. The study highlights STAD’s alignment with 21st-century educational demands, emphasizing its adaptability to diverse subjects, including mathematics, science, and social studies. However, gaps remain in understanding its long-term efficacy, cross-cultural applicability, and integration with emerging technologies like AI and VR. The research underscores the need for future studies to explore these dimensions, ensuring STAD’s relevance in modern, technology-driven classrooms. Implications suggest that educators and policymakers should consider STAD as a viable strategy to enhance collaborative learning, inclusivity, and skill development, ultimately contributing to higher-quality education systems.